Kebijakan National Sword: Respons Tiongkok Dalam Menghadapi Impor Limbah Bahan Baku - Wahyu Setyo Wicaksono; Mohamad Rosyidin; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Rapid economic growth in the People’s Republic of China is caused by many factors. One of the factors is the high number of products exports in which the products come from imported waste raw materials. Unfortunately, the high number of waste raw materials used in the products-processing activities have caused ecological problems in China. These environmental problems have also caused consequential threats to the livelihood of Chinese citizens. This prompted the Chinese Government to ensure its intention to overcome the ecological problems that occurred in China by imposing National Sword Policy. Using the concept of human security, this research aims to explain the factors behind the Chinese Government’s decision to impose the National Sword Policy. This research also tries to explain how the concept of human security plays a significant role in influencing the Chinese Government’s decision to create National Sword Policy. At the end of this research, the author conveys the result of the research that reveals that the National Sword Policy, created by the Chinese Government, is mainly influenced by the concept of human security and the Chinese Government’s idea of peaceful development.